Legal Protection for Kitcar Manufacturing Based on Motor Vehicle Customization Regulations in Indonesia - Okeu Nanda Oktavia; Danyla Faza Lutfia; Fitri Aprianti; Irma Maulida; Rd. Handiriono (Journal of Social Research, 2025)
Car designs owned by industrial design owners have exclusive rights to exercise moral rights and economic rights. However, this right has a certain time limit, as long as the product's design is still under the registrant's ownership. This often causes problems related to industrial designs by other parties who are not entitled to the use of similar designs, such as kitcar production practices in Indonesia. The kitcar certification process typically involves several stages that must be passed by the vehicle assembler or manufacturer to ensure that the vehicle meets applicable standards by testing safety and environmental standards. This study aims to find out the legal protection related to industrial design used in the manufacture of kitcars in Indonesia and to find out the regulations regarding kitcar certification in Indonesia. This study uses a normative juridical approach consisting of two sources, namely primary materials and secondary data. The primary material used in this study is laws and regulations. Meanwhile, the secondary materials used are the results of research interviews, expert opinions in books, journals, and articles related to this research. The results of this study prove that kitcar manufacturing activities are not included in violations, as long as the industrial design used is in accordance with applicable provisions and its legality has been regulated in terms of reviews related to legal protection of industrial design and legal certainty regarding kitcar certification. This kitcar activity is not categorized as a violation as long as the industrial design used in its manufacture has expired its protection period and the nature of the design has become public property. So, the industrial design can be used freely. Kitcar needs to follow several stages of testing that have been regulated in legislation. If all stages of testing have been met, the status of the kitcar can be declared legal.